Surgical strategy for the treatment of craniofacial tumors with intracranial, extracranial and intraorbital extensions - O.I. Palamar; A.P. Huk; E.V. Lukach; D.I. Okonskyi; D.S. Teslenko; B.O. Davydenko (Ukrainian Society of Ophthalmologists, 2023)
Background: Surgical treatment of craniofacial tumors with intracranial, extracranial and intraorbital extensions requires several surgical teams of different specialties (neurosurgery; ear, nose and throat surgery; and eye surgery (for a separate surgical approach)) to be involved. In addition, because craniofacial approaches require creating several surgical fields, the duration of surgery per se is rather long. The conventional transbasal Derome approach is less traumatic than the anterior craniofacial resection and requires no additional dissections of the face. The subcranial approach (a modification of the transbasal Derome approach) may be a low-invasive alternative to the transbasal Derome approach. Purpose: To assess the efficacy of surgical treatment for craniofacial tumors with intracranial, extracranial, and intraorbital extensions. Material and Methods: We retrospectively reviewed the medical records of 88 patients with craniofacial tumors (particularly, 66 malignant tumors and 25 benign tumors). Of the 88 patients, 12 (14%) were treated with the transbasal Derome approach, and 76 (86%), with the subcranial approach (via the frontal sinus). Results: The percentage attributed to total tumor excision (with clear wound margins) was the same (92%; 11/12 and 70/76 patients, respectively) for the groups of patients treated with subcranial and transbasal approaches. Patients with subtotal tumor excision (7/88 or 8%) had malignant tumors, and the rate of subtotal tumor excision was 8% (1/12 and 6/76, respectively) for the groups treated with the former and latter approaches. Mean duration of surgery was significantly shorter in the subcranial approach than in the transbasal Derome approach (291 ± 24 minutes versus 372 ± 48 minutes; р < 0.0000). Conclusion: Craniofacial tumors with intracranial, extracranial and intraorbital extensions can be totally simultaneously excised by transbasal approaches. A modification of the transbasal Derome approach, the subcranial approach (via the frontal sinus) to craniofacial tumors, can be performed easier and faster, is less traumatic, can be lateralized, and showed the same rate of total tumor excision compared to the transbasal Derome approach.